Qualities of effective teachers - Steinhorn, Paul; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2004)
Explains teacher characteristics and behaviors that make the difference in student success, spotlights qualities for new teachers, highlights preservice training and teacher hiring and instill teacher professional development programs
program 1. Building a foundation (37 min.) -- program 2. Managing the classroom (32 min.) -- program 3. Planning and delivering instruction (33 min.)
Title from disc label
Executive producer, John Checkley ; editor, Bill Creed ; camera, Rick Diamond...[et al.] ; sound, Rick Patterson, Rich Pooler
Narrator: Aleta Greene
Keywords: Effective teaching; Teacher effectiveness